P.047 Implications of Gold Coast Criteria in diagnosis of amyotrophic lateral sclerosis in a large subspecialty clinic. (June 2022) - Jewett, G; Khayambashi, S; Frost, GS; Beland, B; Lee, A; Hodgkinson, V; Korngut, L; Chhibber, S
Abstract : Background: Criteria to formalize the diagnosis of amyotrophic lateral sclerosis (ALS) and refine clinical trial populations have evolved. The recently proposed Gold Coast criteria (GCC) are intended to simplify use and increase sensitivity. We evaluated sensitivity of GCC and potential impacts on therapeutic trial enrollment. Methods: We performed a single center retrospective study including patients diagnosed with ALS between 2016 – 2021. We determined criteria met at diagnosis according to revised El Escorial (rEEC), Awaji (AC) and GCC. We compared sensitivity and examined impacts GCC would have on enrollment in landmark ALS trials. Results: We included 203 people with ALS. Sensitivity of GCC (96.1%, 95% confidence interval [CI] = 92.2-98.2%) was significantly higher than rEEC (89.8%, 95% CI 84.6-93.4%, χ 2 = 5.3, p = 0.01) and AC (89.3%, 95% CI 84.1-93.0%, χ 2 = 6.1, p = 0.006). GCC was more sensitive than clinically definite or probable rEEC (47.6%, 95% CI 40.6-54.6%, χ 2 = 117.6, p = < 0.001) and use would result in increased eligibility in landmark therapeutic trials. Conclusions: GCC are more sensitive than rEEC and AC at time of diagnosis in ALS. Use of GCC in our population would expand clinical trial participation and make results more widely generalizable.